Ultrafast non-adiabatic relaxation dynamics of furan theoretically addressed for tr-AttoXAFS - Ziems, K. M.; Severino, S.; Reduzzi, M.; Summers, A.; Sun, H. W.; Chien, Y. H.; Biegert, J.; Gräfe, Stefanie (Optics InfoBase Conference Papers, 2022)
We employ a multi-physics approach comprised of on-the-fly surface hopping and various quantum chemical methods to examine the ultrafast relaxation dynamics of furan induced by a strong-field excitation and measured by attosecond carbon K-edge spectroscopy.
CRIS-Team Scopus Importer:2023-04-20